Effects of Naltrexone on Energy Balance and Hypothalamic Melanocortin Peptides in Male Mice Fed a High-Fat Diet - Panigrahi, Sunil K (J Endocr Soc, 2019)
The hypothalamic melanocortin system composed of proopiomelanocortin (POMC) and agouti-related protein (AgRP) neurons plays a key role in maintaining energy homeostasis. The POMC-derived peptides, α-MSH and β-EP, have distinct roles in this process. α-MSH inhibits food intake, whereas β-EP, an endogenous opioid, can inhibit POMC neurons and stimulate food intake. A mouse model was used to examine the effects of opioid antagonism with naltrexone (NTX) on Pomc and Agrp gene expression and POMC peptide processing in the hypothalamus in conjunction with changes in energy balance. There were clear stimulatory effects of NTX on hypothalamic Pomc in mice receiving low- and high-fat diets, yet only transient decreases in food intake and body weight gain were noted. The effects on Pomc expression were accompanied by an increase in POMC prohormone levels and a decrease in levels of the processed peptides α-MSH and β-EP. Arcuate expression of the POMC processing enzymes Pcsk1, Pcsk2, and Cpe was not altered by NTX, but expression of Prcp, an enzyme that inactivates α-MSH, increased after NTX exposure. NTX exposure also stimulated hypothalamic Agrp expression, but the effects of NTX on energy balance were not enhanced in Agrp-null mice. Despite clear stimulatory effects of NTX on Pomc expression in the hypothalamus, only modest transient decreases in food intake and body weight were seen. Effects of NTX on POMC processing, and possibly α-MSH inactivation, as well as stimulatory effects on AgRP neurons could mitigate the effects of NTX on energy balance.